Saving the girl: A creative reading of Alice Sebold's Lucky and The Lovely Bones. (December 2018) - Kilby, Jane
In the late 1990s, Alice Sebold is writing what will become her phenomenally successful novel The Lovely Bones (2002), but she finds herself having to abandon it in order to write her critically acclaimed rape memoir Lucky (1999). She did not want, she says years later, Susie Salmon (the novel's dead narrator) doing "work for her", but wanted Susie free "to tell her own story". Lucky would be the "real deal" about rape, while The Lovely Bones would be a fantasy. And yet, the memoir and novel are similar in many respects; and nearly identical to begin with. The Lovely Bones opens with the rape, murder and mutilation of a young girl – Susie – while Lucky opens with reference to the girl who was raped, murdered and mutilated in the tunnel Sebold was also raped in. This girl, Sebold maintains, always haunts her. Thus, I will argue, it is not possible to read her novel, which some critics have dismissed as "timid and sentimental", without reading her gritty autobiography; and vice versa it is not possible to read Sebold's rape memoir without reading her novel, which in a complex way bears witness to that unnamed girl, if not for all dead, unnamed girls. The question is, then, how does the intertextuality of Sebold's novel and memoir, and, more broadly, the interrelationship of truth and fantasy, impact on our reading of Sebold's work, especially her memoir? Keywords: Rape, fact, fiction, truth, lie, reading, writing, creative witnessing, wishful thinking, utopia